CHANGES IN THE PHENOTYPE OF VASCULAR WALL CELLS IN CEREBROVASCULAR ATHEROSCLEROSIS IN PATIENTS WITH ISCHEMIC STROKE - Chuiko, N.Ya.; Mankovskiy, D.S.; Kuryk, O.G.; Cherkasova, L.A.; Kisilenko, O.L.; Bazdyrev, K.V.; Verbitskiy, V.V. (World of Medicine and Biology, 2021)
Nowadays, there is a lot of experimental and clinical evidence that atherosclerosis is a chronic inflammatory disease with an autoimmune component. Endothelial damage causes a cascade of inflammatory reactions involving monocytes, macrophages, T-lymphocytes, and vascular smooth muscle cells. In recent years, the pathogenesis of atherosclerosis has been associated with monoclonal proliferation of smooth muscle cells. The article studies the brain arteries’ smooth muscle cells of the vascular walls in atherosclerosis in patients with ischemic stroke. It was determined that when cerebral vessels are damaged by atherosclerosis, there are subpopulations of smooth muscle cells in the vascular wall, which are characterized by the expression of desmin; smooth muscle cells are able to change their phenotype from contractile to synthetic, and this particular change in phenotype is one of the key points in the pathogenesis of atherosclerosis. This change of smooth muscle cells’ phenotype in the endarterium activates proliferation and active synthesis of the connective tissue matrix components, i. e. the modified smooth muscle cells are responsible for the fibrous plaque insula formation.